THE DEVELOPMENT OF SOUND CONSCIOUSNESS IN INDIA - Mishra, Jyoti (International Journal of Research -GRANTHAALAYAH, 2025)
The Indian knowledge tradition is not limited to Vedic and Puranic literature alone, but encompasses numerous fields such as science, mathematics, Ayurveda, yoga, philosophy, and linguistics. Bringing the Indian knowledge system back into the mainstream is a primary need not only for educational institutions but also for Indian society as a whole. The Indian knowledge tradition forms the fundamental basis of both the practical and intellectual aspects of human life, and sound consciousness is the spiritual focal point of human existence.